A Novel Technique for Tarsal Metatarsal Joint (TMTJ) Fusion using Calcaneal Precision Bone Graft: Reducing Morbidity Associated with Bone Graft Donor Site. Issue 4 (November 2022) - Tweedie, Blair P.; Ashford-Wilson, Sarah K.; Mazur, Karolina; Ramaskandhan, Jayasree Ramas; Siddique, Malik S.
Category: Midfoot/Forefoot; Basic Sciences/Biologics; Other Introduction/Purpose: TMTJ fusion has long been used as a treatment for TMTJ disease. Bone grafting has been shown to potentially improve union rates and often the iliac crest as a donor site has been used to achieve this. Indications for bone grafting include severe disease with greater bone loss and deformity, multiple joints being fused or revision surgery. In our paper we report on our experience of TMTJ fusion using localised bone grafting from either the calcaneum or cuneiform. This incorporates a novel operative technique for graft placement which increases contact area for healing and restores foot biomechanics. This may also therefore reduce non-union rate. Additionally, this localised form of bone grafting avoids the morbidity associated with iliac crest donor sites providing a better tolerated procedure. Methods: Twenty patients were included between 2016 and 2019 who underwent fusion of 39 TMTJs in total. Of these 39 joints 9 were first, 16 were second and 14 were third TMTJ. Two of the first TMTJ Fusions were revisions with double plating and bone grafting for non union. Fourteen patients had standard bone grafting and donor sites were as follows; 7 calcaneal, 1 cuneiform, 6 iliac crest. Seven patients had excision of OA joint and bone graft using precision instruments and surgery using our described technique. Locking plates were used in all twenty patients. Post-operative care included a wound check at two weeks, non-weight- bearing in a cast for 6 weeks and then weight-bearing cast for a further 6 weeks. Patients were followed up in clinic to observe radiological and clinical union. Ct scanning employed when delayed union was suspected. Complications with wound healing and infection were also recorded. Results: 15 of patients were female with a mean age of 59. 38 out of 39 fused joints went on to unite. 10 patients were initially assessed in the Specialist Limb Service (SLS) clinic with gait analysis prior to surgery. One non-union was diagnosed on CT scan in the traditional bone graft technique group. Graft was harvested from iliac crest in this case. All other graft sites resulted in fusion of the joint. All seven patients (100%) who had excision and bone graft using precision bone instruments with the new technique had union without delay. One patient underwent removal of metalware due to prominence. This was a revision double plating case. There were no wound healing problems and no postoperative infections. 80% of patients were satisfied with the results of surgery and reported improvement in quality of life. Conclusion: TMTJ fusion with looking plates remains an appropriate treatment for TMTJ disease providing high rates of successful union. Local donor site for bone grafting does not generate inferior outcomes whilst avoiding the morbidity associated with iliac crest harvesting. Additionally, this work presents a novel technique using precision bone graft instruments and cylindrical bone graft to fuse the TMTJ in the presence of OA. This technique generates increased fusion surface area and may provide better restoration of normal foot biomechanics.